Considering Judith: explorations in new historicism : the afterlife of a femme fatale on the borderline between religion and culture, theory and method - Heever, Gerhard van den (Journal for semitics, 2020)
In this essay the ambiguous afterlife of the character Judith and the eponymous book as cultural artefact is explored. The very rich and extensive impact on cultural and social imaginaries by the narrative and character of Judith provides an entry point by which to consider the social, cultural, and ideological work performed by the text. By drawing on a neglected trajectory in the interpretation of Judith, that of its imperialising force, in which Judith functions de facto like other Greek and Roman female deities who act as city protectresses, and later as the Virgin, it is clear that Judith functions as cypher for imperial symbolisms. By employing new historicism and its attendant theoretical assumptions, the figure of Judith becomes the occasion for an experiment in theory and method, on the borderline between cultural discourses and theories of religion. The text is read as a site for the operation of discourse and ideology, and as agency-medium in the imagining of history. When the text is “read” in light of the reception history of both text and image, the text reading denotes the problematic conceptual relationship between theology, religion, and culture. By bringing such questions to bear on the text, this paper explores the borderlines between culture and religion, particularly when done in connection with a text which itself straddles the border between canonical and extracanonical. Judith, the narrative and the figure, serves here as test case for widening the questions that should be brought to bear on ancient “religious” literature.